Create your own home networks - Lazich, Eli (Sams, 2005)
You have a family computer for e-mail and browsing the Internet. Your son and daughter have their own computer for school work and your spouse has a laptop that he or she brings home from work every day. With your family spread out all over the house on their computers, wouldn't it be nice if you could make them all work together? Create Your Own Home Networks is a unique book that will show you how to make your home computers talk to each other while sharing files, music and printers. The most common networking tasks are presented in project-format that doesn't require any in-depth understanding of computer systems or networks beyond that of a typical computer user. You will learn how to setup your computers to: Share printers, files, and Internet connections IM one another instantly Get your e-mail in and out of your network Create a network jukebox Roam your house with wireless You'll also get tips on choosing the right networking equipment, hiding wires and patching holes in your drywall, and when to call the pros. Create Your Own Home Networks is all that you need to get started on creating your very own home network.